The development of Organization of Living Things module through the use of mnemonic and mind mapping using a brain-based learning approach for junior high school Natural Science learning in coastal areas - Jekti Prihatin; Nina Naurah Septiwanti; Kamalia Fikri (JURNAL BIOEDUKATIKA, 2019)
The reading interest of people living in coastal areas is still low. To improve the reading interest, a module that can support learning and attract students' attention are developed through the use of mnemonic and mind mapping based on the Brain-Based Learning (BBL) approach. The objective of the study is to develop a valid, practical and effective Natural Science module that is suitable for coastal communities. This study is a research and development (R&D) which used the Thiagarajan 4-D Model. The stages were limited into three (define, design, and develop) while the other stage (disseminate) was not conducted. The instruments used for data collection consisted of validation sheets, pre-test post-test questions, and student questionnaire response. The preliminary product testing was conducted in a limited number and in a large group setting. The subjects of the study were students in class 7A, 7C, and 7F of SMPN 5 Situbondo in the academic year of 2017/2018. In terms of validity, practicality and effectiveness, the analysis of the module shows that it was very valid, very practical, and quite effective. Therefore, it is suitable to be applied in coastal areas Natural Science learning.